Copper(III) organometallic complexes of non (anti)aromatic and aromatic doubly N-confused porphyrinoids: syntheses and characterization - Panua, Anirban; Velmurugan, Gunasekaran; Comba, Peter; Rath, Harapriya (Dalton transactions, 2025)
The retrosynthetic design and synthesis of three unprecedented doubly N-confused porphyrinoids with tunable aromaticity are reported. The controlled modification of the type of oxidant (chloranil vs. DDQ) led to the isolation of cross-conjugated doubly N-confused porphyrinoid 7 (upon chloranil oxidation) and Hϋckel aromatic porphyrinoid 8, while DDQ oxidation led to the [16]π Hϋckel-antiaromatic porphyrinoid 9. All three hybrid N-confused porphyrinoids 7-9 have been thoroughly characterized via solution-state spectroscopic measurements and in-depth DFT studies. While 7 and 8 could form respective Cu(III) organometallic complexes, porphyrinoid 9 remained unsusceptible to Cu metallation.